Penerapan Model Inkuiri Terbimbing (Guided Inkuiry) Disertai Peta Pikiran Terhadap Hasil Belajar Fisika Siswa Kelas X Man Linggo Sari Baganti - Jannah, Raudhatul; Nuella, Annike (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research is motivated by the lack of physics students learning outcomes. The learning process which tends to be centered on teachers lead students do not actively find ideas. Students are less dare argue or ask questions. This study aims to determine whether the results of learning physics students through Guided Inquiry learning model with Mind Map better than conventional learning in class X MAN Linggo Sari Baganti. This study is quasy experiment, with the study design randomized control group only design. The population in this study is a class X MAN IPA Linggo Sari Baganti Academic Year 2016/2017 consisting of 2 classes (X IPA1 and X IPA2). The conclusion shows that physics student learning outcomes by implementing Guided Inquiry learning model with Mind Map better than conventional teaching in class X MAN Linggo Sari Baganti with average physics student learning outcomes in the cognitive domain the experimental class 83.8 and 78.4 the control class